Music Aptitude, Training, and Cognitive Transfer: A Mini-Review - Wang, Lu (Frontiers in Psychology, 2022)
In this mini-review, the genetic basis of music aptitude and the effects of music training are discussed. The review indicates that regardless of levels of innate ability, experience-induced neuroplasticity can occur as a result of music training. When that happens, it can be expressed as functional or structural brain changes. These changes are often accompanied by improvement in performance in tasks involving auditory analysis. Specifically, a music training effect has been shown to transfer to closely related cognitive domains such as auditory processing (near transfer). There is also some evidence that training has an impact on more distantly related cognitive domains including spatial and linguistic domains. Last, music training has been shown to affect general intelligence via far transfer. In sum, music training can mold behavioral brain development and confers cognitive benefits beyond music.